Diagnóstico das micro e pequenas empresas da cadeia produtiva moveleira da serra gaúcha : importância para o desenvolvimento setorial - Lima, Miguelangelo Geimba De (2001)
The increasing of afluence demands the companies to be competitive and have a deep knowledge about the area wich they are participating. Through the search of management and produtive information, and the analisys of internal and external information, the company could identify strong and weak points , threats and oportunities, alowing the obtaince of competitive advantages. This research shows the result of a close search study about the usage of strategic planning and management technics, setting in evidence the necessity of micro and small furniture companies and furniture supply chain, represented in this case by sub-contract companies. Still looking to accentuate the importance that this study will represent to the setorial development, specially to the furniture companies wich have a big importance due to the report of small utilization of management technics in the sub-contract companies. Through analisys, it was possible to find out some common caracteristics in all 171 conmpanies evaluated, wich are showing likely 'sinalization', such as: - lower level os scholarship (96,5% elementary school, 3% until high school, 0,5% university/college graduration); - external market from Brazilian MPE¿s (5% export products to Mercosul and just 1% export products to Latin America, absenting exportations to other markets); - carefree with modern technics of management, certificates ISO 9000, 14000, MRP, CQT, among others; - carefree with strategic planning; - lower utilization of operacionl procedures, rules and function description; - ignoring the participating of market; - lower utilization of human resources index as a management form; - Small utilization of costs tabs (31%), with a small informatization level (8%) and apllying with non-management form; - low utilization of quality statistics (4%), re-working index (9%), among others. In syntesis, the basis expose that the great marjority of companies don¿t have knowledge about planning and the modern technics of management.